A terrible beauty : a Lady Emily mystery - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2016)
"Lady Emily retreats to her villa on the island of Santorini for a brief respite from London. But when she arrives, the housekeeper informs her that the master of the house has returned--Emily's first husband who died a decade earlier.."--